PARTICIPATION AND CITIZENS 'PARTICIPATION IN PROVIDING EFFICIENT ACTIVITIES OF LOCAL SELF-GOVERNMENT BODIES (IN THE CONTEXT OF DECENTRALIZATION REFORM) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
It is noted that the role of the banking system in the development of Ukraine's economy is exceptional, as it has a multiplier effect on all its other components. Therefore, it is important to solve a set of problems related to its formation and modern organization.The purpose of the article is to study the peculiarities of formation and search for ways to improve the organization of the banking system of Ukraine, taking into account foreign experience.It is noted that the process of formation of the two-tier banking system of Ukraine, as well as most countries, was quite complex and long. In this regard, a set of problems related to its modern organization is considered, and ways to solve them in the context of foreign experience are outlined. It is shown that in the structure of the banking system of Ukraine, in contrast to Germany, Italy, USA and other countries, some types of specialized banks, in particular land and cooperative, whose services are very important for the development of small and medium business and rural areas . It is proved that the tendencies to universalization and uneven distribution by regions of banking institutions do not contribute to improving the efficiency of their operation. The prospects of Internet banking development and the expediency of establishing the Ukrainian Development Bank are emphasized. It is noted that in Ukraine, in contrast to, for example, France, banks have limited membership in various unions or associations, which does not provide a synergy effect and makes it difficult to control their activities. It is shown that banks in Ukraine are not officially members of financial-industrial groups and, unlike banks in the United States, Japan, Germany, South Korea and other countries, do not play a proper role in the development of the national economy. It is noted that non-bank financial institutions in the future may play, as the experience of the United States and the United Kingdom, a significant role in financing business development. It is shown that the role of such institutions and institutions as new legislative acts, the Deposit Guarantee Fund of individuals, the Financial Stability Board, etc. should increase in solving the problems of the organization of the banking system of Ukraine. It is noted that the solution of many problems of the organization of the banking system of Ukraine will depend on how highly organized the NBU will be in it. To do this, it is necessary to: clarify its functions (taking into account the experience of the Bank of France); bring under them a new organizational structure; intensify the work of the Monetary Policy Committee (based on the experience of the United Kingdom and Canada); clearly define reserve assets, independence and forms of interaction with the government (taking into account the experience of Japan and other countries); increase the transparency of activities.Improving the organization of the banking system of Ukraine in accordance with international practices and European standards will help increase its efficiency and successful implementation of the tasks facing it in terms of national economic development.
Keywords: bank (specialized, universal), National Bank of Ukraine, non-bank financial institution, banking system, organization of the banking system.